Biomarkers to Assess Liver Function in Various Types of Liver Diseases - G, Pradeep; B, Vikram; DVHS, Sharma (International Journal of Clinical and Biomedical Research, 2019)
Background: It is estimated that liver diseases are among the top ten killer diseases in India, causing deaths every year. Besides, there are those who suffered from chronic liver problems needing recurrent hospitalization and prolonged medical attention, which leaves them physically, mentally, emotionally and financially devastated. Methodology: The study included (n=80) various liver disease patients admitted to the General Medicine department and controls (n=20) subjects were having normal health within the age group of 30-55 years. Serum levels of bilirubin, Aspartate Transaminase, Alanine Amino Transferase, Alkaline Phosphatase and Gamma Glutamyl Transferase parameters were studied among the subjects suffering from cirrhosis, alcoholic liver disease, viral hepatitis, obstructive jaundice type of liver diseases. Result: The results of this study showed that the increase in serum levels of Bilirubin, AST, ALT, ALP and GGT in various types of liver diseases i.e Obstructive jaundice, Cirrhosis of the liver, Viral hepatitis, Alcoholic Liver disease when compared with controls. Conclusion: Biochemistry laboratory investigations i.e. Liver Function Test (LFT) are a simple, easy measure of tools which can early diagnose the various types of liver diseases. Keywords: Liver diseases; Liver Bio-markers; Liver Function Test.